Can quantifying morphology and TMEM119 expression distinguish between microglia and infiltrating macrophages after ischemic stroke and reperfusion in male and female mice? - Young, Kimberly F. (J Neuroinflammation, 2021)
BACKGROUND: Ischemic stroke is an acquired brain injury with gender-dependent outcomes. A persistent obstacle in understanding the sex-specific neuroinflammatory contributions to ischemic brain injury is distinguishing between resident microglia and infiltrating macrophages—both phagocytes—and determining cell population-specific contributions to injury evolution and recovery processes. Our purpose was to identify microglial and macrophage populations regulated by ischemic stroke using morphology analysis and the presence of microglia transmembrane protein 119 (TMEM119). Second, we examined sex and menopause differences in microglia/macrophage cell populations after an ischemic stroke. METHODS: Male and female, premenopausal and postmenopausal, mice underwent either 60 min of middle cerebral artery occlusion and 24 h of reperfusion or sham surgery. The accelerated ovarian failure model was used to model postmenopause. Brain tissue was collected to quantify the infarct area and for immunohistochemistry and western blot methods. Ionized calcium-binding adapter molecule, TMEM119, and confocal microscopy were used to analyze the microglia morphology and TMEM119 area in the ipsilateral brain regions. Western blot was used to quantify protein quantity. RESULTS: Post-stroke injury is increased in male and postmenopause female mice vs. premenopause female mice (p < 0.05) with differences primarily occurring in the caudal sections. After stroke, the microglia underwent a region, but not sex group, dependent transformation into less ramified cells (p < 0.0001). However, the number of phagocytic microglia was increased in distal ipsilateral regions of postmenopausal mice vs. the other sex groups (p < 0.05). The number of TMEM119-positive cells was decreased in proximity to the infarct (p < 0.0001) but without a sex group effect. Two key findings prevented distinguishing microglia from systemic macrophages. First, morphological data were not congruent with TMEM119 immunofluorescence data. Cells with severely decreased TMEM119 immunofluorescence were ramified, a distinguishing microglia characteristic. Second, whereas the TMEM119 immunofluorescence area decreased in proximity to the infarcted area, the TMEM119 protein quantity was unchanged in the ipsilateral hemisphere regions using western blot methods. CONCLUSIONS: Our findings suggest that TMEM119 is not a stable microglia marker in male and female mice in the context of ischemic stroke. Until TMEM119 function in the brain is elucidated, its use to distinguish between cell populations following brain injury with cell infiltration is cautioned. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12974-021-02105-2.